Pengaruh Modal, Pelayanan Prima, Digital Marketing, dan Harga Jual Terhadap Peningkatan Penjualan UMKM Di Kota Medan - Garry Triskie; Garent Triskie; Jholant Bringg Luck Amelia Br Sinaga; Hotma Mentalita (CV. Ulil Albab Corp, 2026)
This study aims to analyze the effect of capital, service excellence, digital marketing, and pricing on the sales growth of MSMEs in Medan City. The research employs a quantitative approach with a causal associative design. The sample consists of 65 respondents selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS). The results show that capital has a significant effect on sales growth (sig. 0.019 < 0.05; t-value = 2.408), service excellence has a significant effect on sales growth (sig. 0.001 < 0.05; t-value = 3.340), digital marketing does not have a significant effect on sales growth (sig. 0.967 > 0.05; t-value = -0.042), and pricing has a significant effect on sales growth (sig. 0.032 < 0.05; t-value = 2.189). Simultaneously, all independent variables have a significant effect on MSME sales growth (sig. 0.000 < 0.05; F-value = 100.271). This study indicates that capital, service excellence, and pricing play important roles in increasing MSME sales, while digital marketing has not shown a significant effect.